Hemostatic Effect of Vascular Closure Devices (Exoseal®) Versus Manual Compression After Femoral Artery Access - M. Saeed, Ahmed; AH. Ayoob, Mohammed; QK. Alsudany, Mohammed (Public Health of Indonesia, 2025)
Background: From the patient’s perspective, managing vascular access sites after percutaneous procedures remains a clinical challenge. Exoseal® is a novel, bioabsorbable vascular closure device (VCD) developed to seal femoral artery puncture sites following diagnostic or interventional procedures using standard 6–7 F introducer sheaths.Objectives: This study aimed to compare the effectiveness and safety of Exoseal® versus manual compression (MC) for hemostasis in patients undergoing transfemoral coronary angiography and percutaneous coronary intervention (PCI).Methods: A total of 566 patients were enrolled, comprising 464 patients undergoing diagnostic coronary angiography and 102 patients undergoing PCI. Among diagnostic cases, 264 received VCD and 200 received MC. In the PCI group, 51 patients each received VCD or MC. Baseline demographic characteristics age, sex, and BMI were comparable between groups.Results: In the diagnostic group, 58% (154/264) of VCD patients and 60% (122/200) of MC patients were male. Mean age was 59.22 ± 13.33 years (VCD) and 57.98 ± 12.97 years (MC). BMI was 28.92 ± 5.22 (VCD) and 29.34 ± 4.98 (MC). In both diagnostic and interventional groups, VCDs were non-inferior to MC regarding vascular complications. Time to hemostasis and ambulation was significantly shorter in the VCD group.Conclusion: VCDs such as Exoseal® offer a safe and effective alternative to MC for femoral access site closure in coronary procedures. Keywords: vascular access; femoral artery; cardiac catheterization; vascular closure device manual compression; Exoseal®